TRANSUBSTANSIASI DALAM EKARISTI SEBAGAI TANDA KASIH ALLAH BAGI MANUSIA MENURUT DOKUMEN SACRAMENTUM CARITATIS - Kasihiuw, Otis; Turambi, Gerald (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
The presence of Christ in the Eucharist is one of the very important teachings in the Tradition of the Catholic Church. The Eucharist, also known as the Holy Communion, is the pinnacle of Christian life. In the celebration of the Eucharist, the faithful believe that Christ is truly present in the form of Bread and Wine that have been consecrated by the priest. The discussion of this theme is very relevant, as it can help the faithful understand more deeply the meaning of the Eucharist, and provide a clearer understanding of the theological foundations that underpin this teaching. This rejection and the attitude of doubt regarding Christ's presence in the sacrificial Eucharist have led some people to lose their faith, even leaving the embrace of the holy Mother Church. Therefore, we, the authors, are interested and want to explore further the teaching on the presence of Christ in the Eucharist, based on the insights from the Apostolic exhortation of Holy Father Benedict XVI, in the document Sacramentum Caritatis.